2001
DOI: 10.1023/a:1012058107731
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Analysis of bacteria-derived cellular fatty acids was applied to study differences in faecal floras of inbred mice. The bacterial composition of the faecal flora clearly changes with age, whereas the sex does not affect it. Most interestingly, different mouse strains were found to have different faecal floras. This was particularly observed at the age of 17-19 weeks for stool samples of four different mouse strains; the mice were handled identically in identical environments, and the two congenic strains used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Relevant studies in broilers have confirmed increasing bacterial diversity and succession with age, and the current findings are in agreement with this (21,24,29). The increased diversification and succession of the bacterial community structure reflect the development of the immature cecal microflora toward a more mature and stable flora, a characteristic demonstrated in the juveniles of many species, including mice and humans (30,31). Host physiology has been shown to have an impact on the development of the gastrointestinal microbiota (32).…”
Section: Resultssupporting
confidence: 86%
“…Relevant studies in broilers have confirmed increasing bacterial diversity and succession with age, and the current findings are in agreement with this (21,24,29). The increased diversification and succession of the bacterial community structure reflect the development of the immature cecal microflora toward a more mature and stable flora, a characteristic demonstrated in the juveniles of many species, including mice and humans (30,31). Host physiology has been shown to have an impact on the development of the gastrointestinal microbiota (32).…”
Section: Resultssupporting
confidence: 86%
“…Age has been reported as a determinant of microbiota composition in mice [36], [37]. The MHH2009 group contained mice of two different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The bird Sass died several weeks after the collection of faecal samples, but not due to pathogen-related illness, and had not been treated with antibiotics prior to sampling (which can disrupt the GIT community [44], [45]). Subject age has been linked to a shift in the bacterial gut community in humans [46], [47] and mice [48], so it is conceivable that such a community change may be a natural phenomenon. While functional roles of the bacteria detected in this study can only be speculated upon, those bacteria encountered in the kakapo GIT correspond to genera commonly observed in other herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have highlighted differences between bacterial recovery from mucosal biopsies and faecal samples [7], [69], this appears to be due to faecal samples containing not only mucosa-associated bacteria that have been shed into the faeces, but also bacteria that colonize the faecal substrate directly. Community data taken from faecal samples contains a reasonable representation of microbes within the hindgut, and differences in faecal microbiota (both at presence/absence and functional levels) have been shown to reflect differences in the intestinal tract of the host [48], [70], although it must be stressed that they do not provide an exact representation of microbial community structure and function within the intestine itself. Based on unweighted UniFrac analysis it appears that the faecal bacterial communities of adults and chick kakapo are not significantly different, which may indicate a vector for inoculation of kakapo chicks with their parents' microbiota.…”
Section: Discussionmentioning
confidence: 99%